2019
DOI: 10.3961/jpmph.19.166
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Perceived Neighborhood Walkability and Environmental Pollution With Frailty Among Community-dwelling Older Adults in Korean Rural Areas: A Cross-sectional Study

Abstract: ObjectivesThe aim of this study was to evaluate the associations of frailty with perceived neighborhood walkability and environmental pollution among community-dwelling older adults in rural areas.MethodsThe participants were 808 community-dwelling men and women aged 65 years and older in 2 rural towns. Comprehensive information, including demographics, socioeconomic status, grip strength, polypharmacy, perceived neighborhood environment (specifically, walkability and environmental pollution), and frailty, was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Appendix A provides the 17 items and the methods for scoring them. Each item has a possible score from 1 to 4, except for “type of housing,” which is scored from 0 to 1; the total possible score is from 16 to 65, with higher scores indicating better perceived neighborhood environment [ 12 , 25 ]. In addition, the dichotomized variable is coded as “0” for 1–2 points and “1” for 3–4 points [ 12 ].…”
Section: Methodsmentioning
confidence: 99%
“…Appendix A provides the 17 items and the methods for scoring them. Each item has a possible score from 1 to 4, except for “type of housing,” which is scored from 0 to 1; the total possible score is from 16 to 65, with higher scores indicating better perceived neighborhood environment [ 12 , 25 ]. In addition, the dichotomized variable is coded as “0” for 1–2 points and “1” for 3–4 points [ 12 ].…”
Section: Methodsmentioning
confidence: 99%
“…The score ranges from 0 to 15, with a higher score indicating poorer health status. Those scoring 4 or above were classified as frail, and the classification is commonly used in previous studies [ 18 , 19 , 20 , 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…Studies have also shown that age-friendly communities are positively associated with life satisfaction [ 20 ], good self-rated health and a lower likelihood of functional limitations [ 21 , 22 , 23 ], and mental health [ 24 , 25 ]. Although previous studies have demonstrated that some community features, including walkability, green space, and social capital, are negatively related to frailty [ 26 , 27 ], to our knowledge, there is no research on the relationship between holistic assessment including individual- and community-level of age-friendliness of communities (AFC) and frailty. To fill this gap, the current study examined the relationship between holistic AFC and frailty in a large sample of older Chinese people.…”
Section: Introductionmentioning
confidence: 99%